Implementasi Metode Swot dan Lean Canvas Sebagai Upaya Menghadapi Persaingan Bisnis di CV. FJG - Imama, Nuzulia; Hariastuti, Ni Luh Putu (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The growth and development of micro, small and medium enterprises (MSMEs) have an important role in the national economy, including creating jobs and encouraging regional economic growth. CV FJG as one of the MSMEs in the industrial sector faces challenges when its income does not reach its target. To overcome these problems, CV FJG implemented a business development strategy using the IFE (Internal Factor Evaluation) and EFE (External Factor Evaluation) matrix analysis methods, as well as other methods. IFE and EFE matrix analysis helps companies identify and evaluate internal and external factors that influence their performance. Meanwhile, SWOT analysis is used to build strategies based on the strengths, weaknesses, opportunities and threats faced. Lean Canvas enables companies to design more efficient business models and respond more quickly to market developments. Through this approach, CV FJG is expected to increase revenue and achieve predetermined business goals.